2019
DOI: 10.9734/isrr/2019/v8i130092
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an AIDS Education Program on the Knowledge and Attitudes of Physical Therapy Students

Abstract: AIDS (acquired Immunodeficiency syndrome) is a fast spreading pandemic with global affection and has affected lives of multitudes in recent years. The purpose of this paper was to determine the effect of an AIDS education program on physical therapy students’ knowledge about AIDS, attitudes towards people with AIDS and willingness to treat AIDS patients. A sample of 50 physical therapy students’ aged 22 to 28 volunteered to participate in this study. All subjects were pretested and posttested together with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Previous evidence in China has indicated that educational initiatives that assist nursing students in developing empathy [ 10 ], peer interventions combined with standardized patient training [ 11 ], and anti-AIDS discrimination training program [ 12 ], are essential to delivering patient-centered inclusive care to HIV patients. Internationally, studies have revealed that seminar and virtual patient simulation activity focusing on PLWHAs can positively impact nursing students' attitudes [ 13 , 14 ]. Although nursing education programs have made great efforts over the past decade, and the proportion of healthcare providers unwilling to take care of patients with AIDS has declined, nursing practitioners still feel fear and tend to keep a distance from PLWHAs [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence in China has indicated that educational initiatives that assist nursing students in developing empathy [ 10 ], peer interventions combined with standardized patient training [ 11 ], and anti-AIDS discrimination training program [ 12 ], are essential to delivering patient-centered inclusive care to HIV patients. Internationally, studies have revealed that seminar and virtual patient simulation activity focusing on PLWHAs can positively impact nursing students' attitudes [ 13 , 14 ]. Although nursing education programs have made great efforts over the past decade, and the proportion of healthcare providers unwilling to take care of patients with AIDS has declined, nursing practitioners still feel fear and tend to keep a distance from PLWHAs [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%